Moving, cataloguing and preserving Gramsci’s Prison Notebooks - Naldi, Nerio (International Gramsci Journal, 2025)
This essay reconstructs some of the events which, even though not directly concerning either the content or the chronology of the composition of Antonio Gramsci’s Notebooks, crucially marked their existence. The relevant events may be listed in four groups: 1) the January 1934 shipment of some of the notebooks Gramsci had had in the prison in Turi to the clinic in Formia where he was hospitalized and of some others to Rome, to the home address of his sister-in-law Tat’jana (Tatiana) Schucht; 2) the numbering and cataloguing of the Notebooks that Tat’jana Schucht did a few weeks after Gramsci’s death. Special attention will be paid to the results of the skilful analyses carried out by the Istituto centrale per il restauro e la conservazione del patrimonio archivistico e librario on some of the labels that Tat’jana pasted on the notebooks she catalogued; 3) their shipment to Moscow, between 1937 and 1938, and their preservation until they were returned to Rome after the end of the Second World War; 4) the differences in the ways Gramsci’s Notebooks were counted and the different total number that they were said to consist of. The proposed reconstruction will stress the importance of often underestimated data: the presence of a sketchbook among those normally referred to as notebooks; the fact that Tat’jana herself, while numbering thirty-one of Gramsci’s notebooks, did not number two large-format notebooks, which can be assumed to have remained separate from the others for quite some time; and the existence of two other large-format notebooks on which Tat’jana began to prepare, without completing them, a catalogue of the topics and a complete transcription of the notebooks written by Gramsci. It will moreover become clear that the hypotheses put forward by those who have supported the thesis that one or more of the notebooks were subtracted lack solid foundations and are unnecessary.